Phenotypic Heterogeneity in Bacterial Quorum Sensing Systems. Issue 23 (22nd November 2019) - Bettenworth, Vera; Steinfeld, Benedikt; Duin, Hilke; Petersen, Katrin; Streit, Wolfgang R.; Bischofs, Ilka; Becker, Anke
Abstract: Quorum sensing is usually thought of as a collective behavior in which all members of a population partake. However, over the last decade, several reports of phenotypic heterogeneity in quorum sensing-related gene expression have been put forward, thus challenging this view. In the respective systems, cells of isogenic populations did not contribute equally to autoinducer production or target gene activation, and in some cases, the fraction of contributing cells was modulated by environmental factors. Here, we look into potential origins of these incidences and into how initial cell-to-cell variations might be amplified to establish distinct phenotypic heterogeneity. We furthermore discuss potential functions heterogeneity in bacterial quorum sensing systems could serve: as a preparation for environmental fluctuations (bet hedging), as a more cost-effective way of producing public goods (division of labor), as a loophole for genotypic cooperators when faced with non-contributing mutants (cheat protection), or simply as a means to fine-tune the output of the population as a whole (output modulation). We illustrate certain aspects of these recent developments with the model organisms Sinorhizobium meliloti, Sinorhizobium fredii and Bacillus subtilis, which possess quorum sensing systems of different complexity, but all show phenotypic heterogeneity therein. Graphical Abstract: Unlabelled Image Highlights: Review of examples of phenotypic heterogeneity in quorum sensing Review of examples of factors modulating quorum sensing Discussion of potential functions of phenotypic heterogeneity in quorum sensing